Sistem Penempahan Fotografi Estar Art Production Berasaskan Android - Saharudin, Shafiqah Safi; Mohd Yusof, Munirah (Applied Information Technology And Computer Science, 2021)
Android-Based Estar Art Production Booking System is a photography service booking system for Estar Art Production companies that offer photography services for various events and events. This booking system was developed to make it easier for customers to make reservations and to assist administrators in the management of bookings that have been made by customers. The development of this system is based on a prototyping model. Among the activities in this prototype model are identifying the problem statement and system objectives, identifying system requirements, designing the system interface and database. The system was developed using Flutter for application development for client and photographer use while Bracket is used for web development for administrator use and uses PhpMyAdmin as database. This booking system was developed in order to help from the aspect of booking the Estar Art Production photography service and to be able to help from the aspect of photographer work schedule management and bookings that have been made by customers from the beginning of the process to completion to be more organized and efficient.